Analisis Perbandingan Metode Economic Order Quantity (EOQ) Dan Periodic Order Quantity (POQ) Terhadap Pengendalian Persediaan Studi Kasus Pada PT Sriwijaya Abadi Solusindo - Muhammad Reffy Fadilah; Heni Rohaeni Sofyan; Indah Rizki Maulia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Inventory control is one of the important problems faced by companies. Large and small inventories will also cause problems for the company. The aim of this research is to provide suggestions for the best method at PT Sriwijaya Abadi Solusindo for optimizing Thermal Label inventory and to provide order frequency and provide a good level of reorder point and safety stock for ordering Thermal Labels at PT Sriwijaya Abadi Solusindo. By using the Economic Order Quantity (EOQ) and Period Order Quantity (POQ) methods, companies can reduce shipping and inventory storage costs to a minimum. The results of the analysis carried out a comparison between the total costs incurred using the Economic Order Quantity (EOQ) and Period Order Quantity (POQ) methods, it was obtained that the inventory costs between the total costs of PT Sriwijaya Abadi Solusindo and the total costs of the Economic Order Quantity (EOQ) method were IDR 2,669. 210.34, and the total cost using the Period Order Quantity (POQ) method is Rp. 22,344,634. So it can be concluded that the Economic Order Quantity (EOQ) method is the most effective for reducing ordering and storage costs when compared to the Period Order Quantity (POQ) method.